Isolation and Determination of Antimicrobial Activity of Lactic Acid Bacteria from Fermented Fish Product, Pla-Som - Hongsachart, Piyorot (KKU Science Journal, 2016)
Isolation of lactic acid bacteria (LAB) from Pla-Som samples collected from local markets in the area of Nong Khai province found a total of 37 LAB isolates including 8 cocci and 29 rods. Isolated LAB were subsequently determined antibacterial activities against 11 pathogenic bacteria using the disc diffusion method. It was found that the LAB isolate namely, L8-16 was effective against both Gram-negative and Gram-positive bacteria. It exhibited strong inhibition activity against Shigella sp., Pseudomonas sp. P. aeruginosa and moderate inhibition activity against Bacillus megaterium, Bacillus cereus, Escherichia coli and Salmonella Typhi. In addition, the isolate L7-1 also showed strong inhibition activity against S. Typhi and P. aeruginosa and moderate inhibition activity against Staphylococcus aureus, B. subtilis, E. coli and Klebsiella pneumoniae. Overall, the most of LAB isolates inhibited Gram negative bacteria more than Gram-positive bacteria with moderate (11-12 mm) and strong (13-15 mm) inhibition zones. There was only isolate L8-14 showed strong inhibition against B. cereus. Based on these results, isolated LAB would be considered to be potential biopreservatives in Pla-Som fermentation.